Vascular and Neuronal Network Formation Regulated by Growth Factors and Guidance Cues - Wakayama, Yuki; Yamagishi, Satoru (Life, 2023)
Blood vessels and nerves are distributed throughout the body and show a high degree of anatomical parallelism and functional crosstalk. These networks transport oxygen, nutrients, and information to maintain homeostasis. Thus, disruption of network formation can cause diseases. Nervous system development requires the navigation of the axons of neurons to their correct destination. Blood vessel formation occurs via vasculogenesis and angiogenesis. Vasculogenesis is the process of de novo blood vessel formation, and angiogenesis is the process whereby endothelial cells sprout from pre-existing vessels. Both developmental processes require guidance molecules to establish precise branching patterns of these systems in the vertebrate body. These network formations are regulated by growth factors, such as vascular endothelial growth factor; and guidance cues, such as ephrin, netrin, semaphorin, and slit. Neuronal and vascular structures extend lamellipodia and filopodia, which sense guidance cues that are mediated by the Rho family and actin cytosol rearrangement, to migrate to the goal during development. Furthermore, endothelial cells regulate neuronal development and vice versa. In this review, we describe the guidance molecules that regulate neuronal and vascular network formation.
CRIS-Team WoS Importer:2023-03-17